O celowości kary grzywny za wykroczenia - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of this article is to present a model of fine imposed for petty offenses within the scope of its jurisdiction and enforcement. The fine is the primary means of government response to all petty offenses. The share of fines in the overall structure of the penalties imposed for petty offenses is about 90%. The author, through the study of the evolution of a fine, analyzes the solutions relatedto the adjudication of fundamental and substitute fines, their place in the system of sanctions held for petty offenses. The author presents on the one hand the desirabiliy of the fine and indicates its numerous advantages, on the other she indicates its disadvantages, which also have impact on the ongoing legislative changes.
Keywords: grzywna; wykroczenia